2020
DOI: 10.3390/rs12050773
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and Damage Assessment of “Royal” Burial Mounds in the Siberian Valley of the Kings

Abstract: The Valley of the Kings in Tuva Republic, southern Siberia, is arguably one of the most important archaeological landscapes in the eastern Eurasian steppes. Nonetheless, little information exists about the spatial characteristics and preservation conditions of this burial ground consisting of large "royal" mounds. We map the large monuments of the Uyuk Valley's northern river terrace and assess their state of preservation based on high-resolution optical satellite data. The burial site consists of several hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 24 publications
(31 reference statements)
0
15
0
Order By: Relevance
“…In the adjacent mountains that define the valley to the north and south, the backscatter is much more intense. These are accidentally also the areas with few large archaeological features [14], making the successful detection of sites in PALSAR highly unlikely. After mapping these anomalies, we then visited all locations on the ground in order to verify whether or not the similar signature in the PALSAR data stood for a homogenous group of features.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the adjacent mountains that define the valley to the north and south, the backscatter is much more intense. These are accidentally also the areas with few large archaeological features [14], making the successful detection of sites in PALSAR highly unlikely. After mapping these anomalies, we then visited all locations on the ground in order to verify whether or not the similar signature in the PALSAR data stood for a homogenous group of features.…”
Section: Methodsmentioning
confidence: 99%
“…We started analyzing the well-known burial mounds along the northern river terrace based on previous work [14]. With a dual-polarized PALSAR-2 FBD (Fine-Beam Double polarization) image with about 4 m spatial resolution, the structures of Tunnug 1 and Arzhan 5 are well distinguishable, as shown in Figure 4.…”
Section: Finding Known "Royal" Burial Moundsmentioning
confidence: 99%
“…The vast majority of burial mounds on the Eurasian steppes are heavily damaged by looting (Caspari 2018), likely robbed relatively soon after their construction. Recent analysis has shown that in the Uyuk Valley, around 92% of burial mounds suffered from severe looting (Caspari 2020b). Despite the rich material remains recovered from Arzhan 2, the burial was not able to contribute data to questions concerning the inception of Scythian material culture, as the animal style is already fully developed.…”
Section: The Early Iron Age In Tuva and The Tunnug 1 Projectmentioning
confidence: 99%
“…In 1980, M. Gryaznov, a pioneer of research into the origins of the Scythians, noted that he considered three large burial mounds within the landscape of the Uyuk Valley in the Tuva Republic to provide the most promising insights into the earliest Scythian horizon (Gryaznov 1980, 5). The Uyuk Valley in the Tuva Republic, which he dubbed the "Valley of the Kings," boasts over 150 burial mounds, each with a diameter of over 25 m, as well as several extremely large monuments with diameters over 100 m (Caspari 2020b). What is more, there are a few monuments which take the form of relatively flat stone platforms, rather than conical hills; these are the subject of the current research regarding the earliest Scythian material culture.…”
Section: The Early Iron Age In Tuva and The Tunnug 1 Projectmentioning
confidence: 99%
“…Among the most significant archaeological findings from the region is a series of princely burial mounds (kurgans) of the early "Scythian" period. The latter includes the Arzhan and Aldy-Bel cultural horizon encompassing a period from the late ninth to sixth c. BCE (Caspari, 2020). Excavations of these princely burial mounds have generated archaeological and anthropological data of relevance for the interpretation of the Scythian material culture in Siberia and, in general, Central Asia (Caspari et al, 2019;Caspari, Sadykov, Blochin, & Hajdas, 2018;Gryaznov, 1980Gryaznov, , 1984Parzinger, 2006;Zaitseva et al, 2007).…”
Section: Archaeological Context and Site Studymentioning
confidence: 99%